Barriers to diversity among young scientists around the globe: Examining discrimination and harassment at the workplace - Jonas Radl; Shaheen Motala-Timol (GYA Connections, 2022)
This article presents key findings from a survey carried out among GYA members and alumni in 2021 about workplace challenges in science. This survey was implemented by the GYA's Women in Science Working Group, with support by the GYA Office. The two principal domains that the survey set out to cover were 1) workplace policies promoting gender equality, and 2) experiences of discrimination and harassment. This article outlines the key insights gained based on evidence contained in the survey.
Keywords: 300